Kampung boy - Lat, Dato', 1951- ([New York] : [First Second], 2006)
Relates the life experiences, from birth to beginning boarding school, of a boy growing up on a rubber plantation in rural Malaysia
First published in Malaysia in 1979 under the title, Lat, the kampung boy, by Berita Publishing
Keywords: Families -- Malaysia -- Comic books, strips, etc. -- Juvenile fiction; Family life -- Malaysia -- Fiction; Muslims -- Fiction; Country life -- Malaysia -- Fiction; Malaysia -- History -- 20th century -- Fiction; Graphic novels; Biographical fiction; Children's stories -- Pictorial works